PENGARUH STRUKTUR MODAL, STRUKTUR KEPEMILIKAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR KIMIA YANG TERDAFTAR DI BEI - Firnanda Sofiar; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The aim of this study to determine the influences of Capital Structure, Ownership struvture and Profitability toward Companies Value of Chemistry which is listed on Indonesia Stock Excange. Ratio of capital structure is used as the independent variable is the Debt to Equity Ratio (DER). Ownership structure is used as the independent variabel is the institutional (INST). Profitability ratio which is used as independent variabel are return on investment (ROI). While the value companies as dependent variabel measured by ratio price book value (PBV). In this study, the data where financial report and annual report. The sampling taken by purposive sampling, the sample are 5 from 10 companies of chemistry which is listed on Indonesia Stock Excange. Analysis techniques in this study are simple linear, double linear, determinate coefficient, test t (partial), and test F (simultan). Data analysis was used analysis linear agression with the help of software SPSS 21. The results showed that the capital structure partially (t test) no significantly affect the value of the company. Ownership structure has no significant effect the value of the company. Profitability has significant effect the value of the company. The result of simultaneous research (F test) showed no significant influence between capital structure, ownership structure and profitability  together to the value of the company in chemistry  sector listed in Indonesia Stock Exchange. Keyword: Capital Structure, Ownership Structure, Profitability, The Companies Value